Comparison of the efficacy and safety of rivaroxaban and low-molecular-weight heparin in Chinese lung cancer patients with nonhigh-risk pulmonary embolism - Yijun Song; Dawei Yang; Dongni Hou; Jun She; Yuanlin Song (Thrombosis Journal, 2023)
Abstract Background Data that guide selection of differing anticoagulant regimens for specific cancer-associated venous thromboembolism (VTE) are lacking. We aimed to compare the efficacy and safety of rivaroxaban and low-molecular-weight heparin (LMWH) against nonhigh-risk pulmonary embolism (PE) in Chinese lung cancer patients. Methods Four hundred forty-six Chinese lung cancer patients with nonhigh-risk PE who initiated treatment with rivaroxaban or LMWH were identified from Zhongshan Hospital database from 2016 to 2020. The primary outcomes were the composite event of VTE recurrence or major bleeding, and all-cause mortality. The secondary outcomes were VTE recurrence, major bleeding and clinically relevant non-major bleeding (CRNMB). Propensity score matching was used to balance baseline covariates. We conducted sensitivity analysis by stabilized inverse probability of treatment weighting and competing risk analysis by a Fine and Gray subdistribution hazard model. Results In propensity score-matched cohorts, rivaroxaban was similar to LMWH in the risks of the composite outcome (hazard ratio (HR), 0.73; 95% confidence interval (CI), 0.45–1.21; P = 0.22), VTE recurrence (HR, 0.69; 95% CI, 0.36–1.34; P = 0.28), major bleeding (HR, 0.79; 95% CI, 0.37–1.68; P = 0.54) and CRNMB (HR, 1.13; 95% CI, 0.62–2.09; P = 0.69). All-cause mortality was significantly lower in rivaroxaban group than LMWH group (HR, 0.52; 95% CI, 0.36–0.75; P < 0.001). The primary and secondary outcomes favored rivaroxaban over LMWH in all the subgroups expect for central PE and intermediate-risk PE. The sensitivity analysis yielded similar results, and competing risk analysis was in accordance with the primary findings. Conclusions Rivaroxaban might be a promising alternative to LMWH as initial treatment for nonhigh-risk PE in lung cancer patients.